1954
DOI: 10.1017/s0021859600044804
|View full text |Cite
|
Sign up to set email alerts
|

Placement of fertilizers for potatoes planted by machines

Abstract: A two-row hand-dropping potato planter was modified by adding fertilizer equipment. The machine was used in thirty-three experiments in 1951 and 1952 to plant potatoes from flat land and compare broadcast dressings of granulated compound fertilizer with dressings placed near to the seed.Fertilizer placed either in one band at the side and below the level of the seed, or in contact with the seed, gave consistently higher yields than broadcast dressings. Broadcast fertilizer gave yields similar to those given by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1954
1954
1985
1985

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Many workers have reported delayed emergence and poor early growth associated with high concentrations of fertilizer salts close to the seed, especially in dry springs (Cooke, 1949;Cooke, Jackson & Widdowson, 1954;Baldwin, 1963). Damage to early growth by fertilizer nitrate ions has been suggested by Widdowson, Penny & Cooke (1960) and injurious effects of ammonia by Warren (1962).…”
Section: Methodsmentioning
confidence: 99%
“…Many workers have reported delayed emergence and poor early growth associated with high concentrations of fertilizer salts close to the seed, especially in dry springs (Cooke, 1949;Cooke, Jackson & Widdowson, 1954;Baldwin, 1963). Damage to early growth by fertilizer nitrate ions has been suggested by Widdowson, Penny & Cooke (1960) and injurious effects of ammonia by Warren (1962).…”
Section: Methodsmentioning
confidence: 99%
“…to the right-hand side of the centre line of the experiment served as a guide to the tractor driver. An experimental potato planter fitted with an end-delivery fertilizer mechanism which was built by the National Institute for Agricultural Engineering (described by Cooke et al 1954) was used to plant seed and place fertilizer as required. After the first two rows had been planted the furrows served as a guide.…”
Section: Methods Of Laying Down the Experimentsmentioning
confidence: 99%
“…Experimental work showed that considerable improvements in fertilizer efficiency could be obtained for some row crops and for potatoes by adopting suitable placement techniques (Cooke & Widdowson 1953;Cooke, Jackson & Widdowson, 1954). In these earlier experiments comparisons between placing and broadcasting were made using granulated PK or NPK compound fertilizers.…”
mentioning
confidence: 99%
“…In temperate and subtropical countries, suitable fertilizer placement has improved the yields of some crops (Long and Sherbakoff, 1951;Cooke et al, 1954) and has controlled 'scorch' due to N and K in compound fertilizers (Wahhab et al, 1957;Reith, 1974). In the tropics, however, better fertilizer placement practices for yams are yet to be determined (Irving, 1956;Stephens 1960;Hauck, 1974).…”
Section: Introductionmentioning
confidence: 99%